PENGARUH KUALITAS LAYANAN DAN PENGALAMAN PELANGGAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN KOPI KAPLING DI KUDUS - Azka Syams Ghiffari; Nurul Rizka Arumsari (Universitas Dharmawangsa, 2026)
The purpose of this study is to analyze the influence of service quality and customer experience on loyalty through customer satisfaction at Kopi Kapling in Kudus. The approach used in this study is a quantitative approach. The sample was 110 Kopi Kapling customers and sampling used a purposive sampling method. The data collection technique used in this study was a questionnaire method. The data analysis technique used was AMOS 24. The results showed that service quality had a positive and significant effect on Kopi Kapling customer loyalty. Customer experience had a positive and significant effect on Kopi Kapling customer loyalty. Service quality had a positive and significant effect on Kopi Kapling customer satisfaction. Customer experience had a positive and significant effect on Kopi Kapling customer satisfaction. Customer satisfaction did not affect Kopi Kapling loyalty.